Conservative When Crowded: Social Crowding and Consumer Choice - Maeng, Ahreum; Tanner, Robin J.; Soman, Dilip (Journal of Marketing Research, 2013)
Does the mere crowdedness of the environment affect people's choices and preferences? In six studies, the authors show that social crowdedness not only leads to greater accessibility of safety-related constructs but also results in greater preference for safety-oriented options (e.g., preferring to visit a pharmacy to a convenience store), being more receptive to prevention- (rather than promotion-) framed messages, and being more risk averse with real money gambles. In support of the authors’ underlying avoidance motivation perspective, these effects are mediated by participants’ net prevention focus and are attenuated when the crowd in question consists of in-group members. The authors close by discussing the practical and theoretical implications of the results.